GROWTH CIRCLE PATTERNS IN THE OTOLITH OF THE GRAY FISH (Osteochilus melanopleurus) FROM THE SIAK AND KAMPAR RIVERS - Sinaga, Martianna; Eddiwan, Eddiwan; Windarti, Windarti; Asiah, Nur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
Osteochilus melanopleurus can be found in the Siak and Kampar Rivers. The Kampar Rivers waters are better than that of the Siak River and it affects the growth of the fish. The growth pattern is reflected in the pattern of otolith growth rings. The research aims to understand the pattern of otolith growth rings of the O. melanopleurus from both rivers has been conducted from January to February 2021. There were 55 fishes captured (28 males and 27 females). The otolith was taken using tweezers and shaved manually using a soft grindstone. The dark growth ring pattern was investigated using a binocular microscope. Results showed the size of fish captured was 220 to 360 mm from Siak River and 310 to 370 mm from Kampar River. In the fish with the same standard length, the size of the otolith from the Siak River is heavier and longer than that of the Kampar River, which means that fish growth from the Kampar River is better than that of the Siak River. The length of an otolith from Siak River ranged from 1.875 – 3.275 mm, the width was ranged from 1.575–2.75 mm and the weight of otolith was 0.0039 – 0.0098 g, while the length of an otolith from Kampar River ranged from 2.375–3.275 mm, the width was ranged from 1.85–2.575 mm and the weight of otolith was 0.0042 –0.0076 g. The maximum number of the dark ring in the otolith from the Siak River was 4 and Kampar River was 2. The distance between the nucleus and the first dark ring of fish from both rivers was varied from 0.1–0.525 mm, and there was no special pattern. This fact indicates that the first dark ring was formed individually and they were not formed by a periodical incidents during the fish life.